PENERAPAN AKTIVITAS QUICK ON THE DRAW DALAM MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X MOTOR CYCLE (MC) SMK TARUNA SATRIA PEKANBARU - Riyuni anggita; Syofni '; Susda Heleni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve the learning process and increase the student’s mathematics learning outcomes through the implementation of the Quick on The Draw Activity in Cooperative Learning of STAD. This type of research is the Classroom Action Research with two cycle. The research was conducted in class X MC in the second semester of the 2015/2016 academic year with the subject of as many as 28 students, consist of 28 boys. The research instrument consists of learning devices and instrument data collectors. Learning device used in this research is the Syllabus, Lesson Plan, Worksheet and Questions Card. The instrument data collector used in this research is the observation sheet and math achievement test. Data analysis technique used is descriptive statistical analysis. Based on the result of the research showed that implementation of learning process on cycle II had happened improvement from implementation on cycle I. Weakness on cycle I is improved on implementation cycle II according with planning of improvement after reflection cycle I. Number of students that reach Minimum Mastery Criteria increase from basic score to daily test II. The number of students who reach Minimum Mastery Criteria on basic scor, daily test I and daily test II are respectively 13 person (46,4%), 14 person (50%) and 21 person (75%). Results of this research indicates that application of the Quick on the Draw Aktivity in Cooperative Learning of STAD can improve learning process and increase mathematics learning outcomes from the students at class X MC (Motor Cycle) SMK Taruna Satria Pekanbaru in the second semester academic years 2015/2016 at Basic Competencies 6.2 Identify the properties of a rectangle, square, trapezoid, parallelogram, rhombus and kite and Basic Competencies 5.1make a chart completion system set linear inequality, 5.2 Determines the mathematical model of word problems, 5.3 determines the optimum value of a system of linear inequalities, 5.4 apply accurate line .Key Words: Cooperative Learning of STAD, Quick on the Draw Aktivity, Learning Process, student’s mathematics learning outcomes, Classroom Action Research.2